Eosinophilic Esophagitis in Esophageal Atresia - Krishnan, Usha (Frontiers in Pediatrics, 2019)
Recent studies have reported a higher prevalence of eosinophilic esophagitis in children with esophageal atresia. Under recognition of eosinophilic esophagitis in these patients may lead to excessive use of antireflux therapy and an escalation of interventions, including fundoplication, as symptoms may be attributed to gastroesophageal reflux disease. In addition, long-term untreated eosinophilic esophagitis may lead to recurrent strictures due to transmural esophageal inflammation, necessitating repeated dilatations. Eosinophilic esophagitis should be considered when children with esophageal atresia show persistent symptoms on standard antireflux treatment, increasing dysphagia, and recurrent strictures. Treatment has been found to not only significantly reduce intraepithelial eosinophil count, but also to improve symptoms, and to lower the occurrence of strictures and the need for dilatations. Future prospective studies are warranted in this area